Acid leaching of chromite-bearing nickeliferous laterite from Rockhampton, Queensland (The Australasian Institute of Mining and Metallurgy, 1986)
Mineralogical analysis of a nickeliferous laterite from the Rockhampton region shows that the nickel is largely associated with the manganese wad and opaline silica. The laterite also contains an appreciable chromite content (about 12 per cent Cr2O,) although this tends to be poorly liberated.Leaching with hydrochloric or sulphuric acid, at atmospheric pressure at the boiling point is non-selective with respect to iron dissolution.The degree of dissolution increases as the acid concentration and retention time are increased; cobalt dissolution requires less aggressive conditions than does the dissolution of an equivalent amount of nickel.Leaching with sulphuric acid at elevated temperatures and pressures leads to a minimum amount of iron dissolution, is rapid, and requires a reduced acid addition rate. Nickel and cobalt recovery from the clarified leachate would be simplified because of the leach selectivity.Pressure leaching appears to be the most practical route for treating the Rockhampton laterite. The economics of processing would be made more attractive by the recovery of a chromium concentrate from the leach residue. This would typically contain about 45 per cent Cr2O, and could be used as a source of chromium chemicals.